Organotin Speciation Analysis Based on Liquid or Gas Chromatography - Alahmadi, S.M. (Asian Journal of Chemistry, 2011)
Organotin compounds have been used on a global scale for many decades now and thus have become global environmental contaminants. These compounds are highly toxic and deleterious effects on numerous organisms have been demonstrated. Several analytical methods for the determination of organotin compound in environmental (e.g., water, sediment and shellfish) have been developed. Analysis of organotin species in the environment needs highly selective and sensitive methods. This paper reviews the organotin speciation analysis based on liquid or gas chromatography.